Evaluation and transcriptomic and metabolomic analysis of the ability of Auricularia heimuer to utilize crop straw - Di Zhang; Yuchen Liu; Ying Li; Guosheng Jiang; Mingzhu Meng; Jihua Wang (PeerJ)
Auricularia heimuer is an important edible fungus, and the choice of its cultivation medium is very important to improve the yield and quality. Traditionally, A. heimuer mostly uses wood chips as cultivation substrate, but with the increase of agricultural waste, exploring agricultural straw as an alternative substrate has become a research hotspot. In this study, a wild A. heimuer strain W-ZD22 with good adaptability to straw matrix was used to measure mycelia growth characteristics and extracellular enzyme activity. Transcriptomics and non-targeted metabolomics methods were used to compare the effects of mycelia using agricultural straw matrix and wood chips matrix. It was found that the lignin enzyme activities of corn straw and wood chips were similar. By transcriptomic and metabolomic analysis, we further analyzed the transcription profiles of A. heimuer mycelia grown in different substrates (straw and corn stalk, straw and sawdust, corn stalk and sawdust), and identified 5,149, 2,740 and 2,933 different expression genes (DEGs), respectively. The three control groups had a total of 526 gene variants. The top 20 pathways with the highest concentration of DEGs mainly involved glyoxylate and dicarboxylate metabolism, glycine, serine and threonine metabolism, glycolysis/gluconeogenesis, pyruvate metabolism, oxidative phosphorylation, endoplasmic reticulum protein processing and ribosome. In order to further understand the similarity of enzyme activity of Auricularia mycelium on corn stalk and wood chips, metabolomic analysis of substrate of corn stalk and wood chips was conducted. It was found that different metabolites were significantly enriched in starch and sucrose metabolism, glutathione metabolism, carbon metabolism and other pathways, which provided theoretical basis for efficient comprehensive utilization of corn stalk in auricularia growth.